Brain gray matter correlates of extraversion: A systematic review and meta‐analysis of voxel‐based morphometry studies - Lai, Han (Hum Brain Mapp, 2019)
Extraversion is a fundamental personality dimension closely related to an individual's life outcomes and mental health. Although an increasing number of studies have attempted to identify the neurostructural markers of extraversion, the results have been highly inconsistent. The current study aimed to achieve a comprehensive understanding of brain gray matter (GM) correlates of extraversion with a systematic review and meta‐analysis approach. Our review showed relatively high interstudy heterogeneity among previous findings. Our meta‐analysis of whole‐brain voxel‐based morphometry studies revealed that extraversion was stably associated with six core brain regions. Additionally, meta‐regression analyses identified brain regions where the associations of extraversion with GM volume were modulated by gender and age. The relationships between extraversion and GM structures were discussed based on three extraversion‐related functional systems. Furthermore, we explained the gender and age effects. Overall, our study is the first to reveal a comprehensive picture of brain GM correlates of extraversion, and the findings may be useful for the selection of targeted brain areas for extraversion interventions.